2004
DOI: 10.1128/cdli.11.5.897-900.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Serological Conversion as a Risk Factor for Development of Leprosy among Household Contacts

Abstract: Although the prevalence of leprosy has declined over the years, there is no evidence that incidence rates are falling. A method of early detection of those people prone to develop the most infectious form of leprosy would contribute to breaking the chain of transmission. Prophylactic treatment of serologically identified high-risk contacts of incident patients should be an operationally feasible approach for routine control programs. In addition, classification of high-risk household contacts will allow contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
25

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 10 publications
6
72
0
25
Order By: Relevance
“…This assumption is further supported by the HHCs data, in which 13% tested positive for IgM anti-PGL-I, a higher percentage than that observed in TT patients, with an increasing prevalence of positive results for MB forms of leprosy. These results further corroborate other studies that demonstrated anti-PGL-I seropositivity is a high risk factor for the development of disease in HHCs, mainly contacts of MB ICs (Douglas et al 2004, Goulart et al 2008). …”
Section: Discussionsupporting
confidence: 82%
“…This assumption is further supported by the HHCs data, in which 13% tested positive for IgM anti-PGL-I, a higher percentage than that observed in TT patients, with an increasing prevalence of positive results for MB forms of leprosy. These results further corroborate other studies that demonstrated anti-PGL-I seropositivity is a high risk factor for the development of disease in HHCs, mainly contacts of MB ICs (Douglas et al 2004, Goulart et al 2008). …”
Section: Discussionsupporting
confidence: 82%
“…In a prospective study, healthy HC with leprosy were followed-up for 12 years. The authors found that APGL-I-positive individuals had 7.65 times higher risk of exhibiting leprosy signs than the APGL-I-negative individuals, and they had a much higher risk for developing MB leprosy (34.4 times) than that for developing PB leprosy (3.52 times) (15) . These results indicate that in the eventual initiation of chemoprophylaxis for HC by the World Health Organization (WHO) (16) , APGL-I-positive HC would be the key focus for reducing leprosy transmission rates.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the presence of antibodies against PGL-I in contacts was associated with a relative risk factor of six times that of negative contacts in Uberlândia (Goulart et al 2008). An examination of serum samples collected from patient contacts in the Philippines also indicated that elevated or rising antibody levels against PGL-I and LID-1, a chimeric fusion protein comprising ML2331 and ML0405, were predictive of the clinical onset of leprosy (Douglas et al 2004, Duthie et al 2007). The time benefit over clinical diagnosis provided by recognising elevated anti-LID-1 IgG levels was estimated to be approximately nine months (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This seropositive but asymptomatic group is perhaps the most interesting to analyse from the viewpoint of reducing infectious reservoirs and the transmission cycle, but has been largely included only serendipitously in prior studies by virtue of being enriched for HHC (i.e., more HHC are seropositive than the general population, although they have typically been included in studies because they are contacts and not because they are seropositive). Although antibody responses in asymptomatic individuals will likely be lower than in patients with high M. leprae burdens, elevated antibody responses appear to indicate an increased risk of developing leprosy, particularly with responses that increase over time (Douglas et al 2004, Duthie et al 2007 (Fig. 1A).…”
Section: Discussionmentioning
confidence: 99%